PENGARUH PRICE, SOCIAL EFFECT DAN PERSONAL INFLUENCETERHADAP KEPUTUSAN PEMBELIAN SEPATU FUTSALMEREK SPECS (STUDI EMPIRIK PADA KONSUMENSEPATU FUTSAL MEREK SPECS DI KOTA PONTIANAK) - B11110148, Retno Susanti (Jurnal Manajemen Update, 2015)
This study aimed to identify and analyze the influence of the price, social effects and personal influence on purchasing decisions among the consumer of SPECS brand futsal shoes in Pontianak. This study was designed as an explanatory research. The population of this study are consumer in Pontianak who use and know various information about the SPECS brand futsal shoes by print media, electronic media or social interaction. This study was using purposive sampling, then elected a sample size 100 respondents were recorded in 2014. The analysis technique used is multiple linear regression analysis by SPSS version 16.0. The results based on multiple linier regression analysis showed that price, social and personal effects of influence to the futsal shoesâ€™s purchase decisions in the SPECS brand consumers in Pontianak, with a significance value of 0.000 and R2 value of 66.3%, while the rest amountedÂ  33.7% were other factors which are not examined in this study. Keywords: price, social effects, personal influence, and purchase decision